Las tramas de un estudio cualitativo en salud mental y violencia política. Lecciones aprendidas (2015)
ABSTRACT: Describe methodological learning from a qualitative research about mental health and political violence with Colombian peasant communities from San Francisco, Colombia, in order to contribute to future explorations where ethics is relevant epistemological perspective in this field. Methodology: A comparison was performed between initial methodological design with the settings and methodological decisions resulting from the study development and other associated dynamics. Results: Comparison between initial design and adjustments and progressive changes identifies the qualitative research methodological design like a process that moves from an imagined research into a embodied research derived from interaction between subjects. Research about mental health and political violence allows knowing this flexible nature related to key ethics elements for methodological decisions as place of the researcher and the participants, legitimacy of facilitators, co-production of knowledge and unconventional research strategies. Conclusion: Partiality of knowledge in qualitative research, the involvement of subjects and design flexibility are not deny their trustworthiness. On contrary, these features guarantee a process that transcends the uncritical adherence to methods.